IMPROVING JUNIOR HIGH SCHOOL STUDENT’S LEARNING OUTCOMES THROUGH INTERACTIVE MULTIMEDIA OF BLOOD CIRCULATION SYSTEM - Dea Damar Wahyu Pradana; Mohammad Budiyanto; Enny Susiyawati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This research aimed to describe the improvement of junior high school student’s learning outcomes after the implementation of interactive multimedia of blood circulation system. This research used a One-Group Pretest-Posttest Design that involved 58 students grade VIII MtsN 4 Sidoarjo. The results of the research showed that the results of the N-Gain grade VIII A students showed that 65,5% of students received a high category score. The N-Gain results of Grade VIII B students showed that 55,2% of students received high categorical scores. Based on the results of the research, it concluded that the interactive multimedia of blood circulation system can improve students’ learning outcomes.   Keywords: learning media, interactive multimedia, learning outcomes.